Titanium Nanoparticles Enhance Production and Suppress Stabilin-1-Mediated Clearance of GDF-15 in Human Primary Macrophages - Silva-Bermudez, Lina S.; Sevastyanova, Tatyana N.; Schmuttermaier, Christina; De La Torre, Carolina; Schumacher, Leonie; Klüter, Harald; Kzhyshkowska, Julia (Frontiers in Immunology, 2021)
Macrophages are key innate immune cells that mediate implant acceptance or rejection. Titanium implants degrade over time inside the body, which results in the release of implant wear-off particles. Titanium nanoparticles (TiNPs) favor pro-inflammatory macrophage polarization (M1) and lower tolerogenic activation (M2). GDF-15 regulates immune tolerance and fibrosis and is endocytosed by stabilin-1. How TiNPs affect the healing activities of macrophages and their release of circulating cytokines is an open question in regenerative medicine. In this study for the first time, we identified the transcriptional program induced and suppressed by TiNPs in human pro-inflammatory and healing macrophages. Microarray analysis revealed that TiNPs altered the expression of 5098 genes in M1 (IFN-γ-stimulated) and 4380 genes in M2 (IL-4–stimulated) macrophages. 1980 genes were differentially regulated in both M1 and M2. Affymetrix analysis, confirmed by RT-PCR, demonstrated that TiNPs upregulate expression of GDF-15 and suppress stabilin-1, scavenger receptor of GDF-15. TiNPs also significantly stimulated GDF-15 protein secretion in inflammatory and healing macrophages. Flow cytometry demonstrated, that scavenging activity of stabilin-1 was significantly suppressed by TiNPs. Confocal microscopy analysis showed that TiNPs impair internalization of stabilin-1 ligand acLDL and its transport to the endocytic pathway. Our data demonstrate that TiNPs have a dual effect on the GDF-15/stabilin-1 interaction in macrophage system, by increasing the production of GDF-15 and suppressing stabilin-1-mediated clearance function. In summary, this process can result in a significant increase of GDF-15 in the extracellular space and in circulation leading to unbalanced pro-fibrotic reactions and implant complications.